2012
DOI: 10.1111/j.1471-0307.2012.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphates as inhibitors of surface mould growth on hard cheese during ripening

Abstract: A novel treatment using polyphosphates to protect cheeses against superficial mould growth was assayed. The treatments were: control commercial paint with natamycin (I), commercial paint based on polyvinyl–water (II), immersion in a saturated solution of polyphosphate (III), immersion and commercial paint (IV), commercial paint of polyphosphate solutions (V) and immersion and commercial paint of a saturated solution of polyphosphates (VI). The cheeses were ripened for 6 months. Superficial mould growth was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that the fungus was able to grow and produce high amounts of OTA in dry-cured ham-based medium under a wide range of conditions (Vipotnik et al, 2017). The inability of the fungus to produce OTA in sausage-based media is maybe due to the composition of this meat product, either by the effect of natural composition (lipid and protein contents) or by the effect of added compounds such as wine, garlic, red pepper and polyphosphates (Gonzales-Barron et al, 2015;Suarez, Frison, de Basilico, Rivera, & Reinheimer, 2005;Suarez, Tremmel, Rivera, Reinheimer, & Meinardi, 2012), which are not present in drycured ham, and might have an inhibitory effect on OTA production ability.…”
Section: Evaluation Of Biocontrol Effect In Dry-fermented Sausagementioning
confidence: 99%
“…It has been demonstrated that the fungus was able to grow and produce high amounts of OTA in dry-cured ham-based medium under a wide range of conditions (Vipotnik et al, 2017). The inability of the fungus to produce OTA in sausage-based media is maybe due to the composition of this meat product, either by the effect of natural composition (lipid and protein contents) or by the effect of added compounds such as wine, garlic, red pepper and polyphosphates (Gonzales-Barron et al, 2015;Suarez, Frison, de Basilico, Rivera, & Reinheimer, 2005;Suarez, Tremmel, Rivera, Reinheimer, & Meinardi, 2012), which are not present in drycured ham, and might have an inhibitory effect on OTA production ability.…”
Section: Evaluation Of Biocontrol Effect In Dry-fermented Sausagementioning
confidence: 99%
“…They are mainly studies on diffusion and/or antimicrobial activity of natamycin in model systems. There is also another group of articles, which are studies on the effect of treatment with natamycin, alone or in combination with other antimicrobial agents on cheese features (e.g., De Oliveira, De F atima Ferreira Soares, Pereira, & De Freitas Fraga, 2007;Dos Santos Pires et al, 2008;Fajardo et al, 2010;Hanu sov a, Dobi a s, & Vold rich, 2012;Hanu sov a et al, 2010;Kallinteri, Kostoula, & Savvaidis, 2013;Mann & Beuchat, 2008;Oll e Resa, Gerschenson, & Jagus, 2014a;Oll e Resa, Jagus, & Gerschenson, 2014b;Ramos et al, 2012;Su arez, Tremmel, Rivera, Reinheimer, & Meinardi, 2012;Ture, Eroglu, Ozen, & Soyer, 2011;Var, Erginkaya, Güven, & Kabak, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Despite these considerations, it is important to emphasise that phosphates are Generally Recognised as Safe (GRAS) compounds (Suárez et al . 2012). According to the US Food and Drug Administration (FDA), none of the GRAS phosphates pose intrinsic harm, and their use in foods does not present a hazard when the total phosphorus intake, along with intakes of calcium, magnesium, vitamin D and other nutrients, remains within satisfactory levels (FDA 1975; Gutiérrez 2013).…”
Section: Discussionmentioning
confidence: 99%